Comparative Study of Bacterial Isolates from Different Clinical Specimens in a Tertiary Care Hospital - Baral, Soma Kanta; Acharya, Kailash Nath; Shrestha, Ram Krishna; Paudel, Deliya; Shrestha, Gita; Regmi, Himanshu; Bajracharya, Upsal Bahadur; Shrestha, Muja; Nakarmi, Rajiv; Simkhada, Eebaraj (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Antimicrobial resistance (AMR) is a critical global health threat, particularly in resource-limited settings. Continuous local surveillance of bacterial isolates and their resistance patterns is essential for guiding evidence-based antimicrobial therapy and infection control strategies. Consequently, the aim of this research is to characterize bacterial isolates from different clinical specimens in a tertiary care hospital and analyze their antimicrobial resistance patterns. Method: A retrospective cross-sectional study was conducted at Manmohan Memorial Teaching Hospital, Kathmandu, from July 2024 to June 2025. A total of 15,525 clinical specimens including urine, sputum, pus, blood, and other body fluids, were processed using standard microbiological procedures. Bacterial identification was performed using colony morphology, Gram staining, and biochemical tests. Antimicrobial susceptibility testing (AST) was performed using the modified Kirby-Bauer disk diffusion method according to Clinical Laboratory Standards Institute (CLSI) 2023 guidelines. The Multiple Antibiotic Resistance (MAR) index was calculated for each isolate. Result: Of 15,525 specimens processed, 1,475 (9.5%) showed significant bacterial growth. Escherichia coli (52.6%) predominated, followed by Klebsiella pneumoniae (18.3%) and Staphylococcus aureus (8.0%). E. coli demonstrated high resistance to cefixime (59.9%) and ceftazidime (73.3%), while S. aureus exhibited 51.6% methicillin resistance. Over 66% of isolates demonstrated a MAR index ≥0.2, indicating the bacteria originated from an environment where antibiotics are frequently used. Gram-negative organisms showed significantly higher resistance rates to third-generation cephalosporins and fluoroquinolones compared to Gram-positive organisms. Conclusion: This study documents concerning levels of antimicrobial resistance among bacterial isolates at the tertiary care hospital, observing a predominance of isolates with a MAR index ≥0.2, multidrug-resistant Gram-negative bacilli, and methicillin-resistant Staphylococcus aureus (MRSA). These findings emphasize the urgent need for routine AMR surveillance, updated empirical treatment guidelines, and the implementation of hospital-based antimicrobial stewardship and infection control programs